Copper-catalyzed oxidative coupling of quinoxalin-2(1H)-ones with alcohols: access to hydroxyalkylation of quinoxalin-2(1H)-ones - Fu, Junhao; Yuan, Jinwei; Zhang, Yue; Xiao, Yongmei; Mao, Pu; Diao, Xiaoqiong; Qu, Lingbo (ORGANIC CHEMISTRY FRONTIERS, 2018)
An efficient copper-catalyzed protocol for the synthesis of hydroxyl-containing quinoxalin-2(1H)-ones from the radical reaction of quinoxalin-2(1H)-ones with alcohols was developed with moderate to good yields. Quinoxalin-2(1H)-ones were coupled with alkyl radicals through direct catalytic functionalization of the sp(3) C-H bond of alcohols. The methodology demonstrates a broad substrate scope, excellent functional group tolerance, high atom economy and high efficiency, thus enabling the preparation of diverse potentially valuable hydroxyl-containing quinoxalin-2(1H)-ones.